A novel EML4-ALK variant: exon 6 of EML4 fused to exon 19 of ALK - Penzel, Roland; Schirmacher, Peter; Warth, Arne (Journal of thoracic oncology, 2015)
Introduction: Cytotoxic chemotherapy remains the mainstay of treatment for most patients with advanced disease. Recently, anaplastic lymphoma kinase (ALK) expression as a major target for successful treatment with ALK inhibitors was detected in a subset of non-small-cell lung carcinomas, usually as a result of echinoderm microtubule-associated protein-like 4 (EML4)-ALK rearrangements. Although the chromosomal breakpoint within the EML4 gene varied, the breakpoint within ALK was most frequently reported within intron 19 or rarely in exon 20. Therefore, the different EML4-ALK variants so far contain the same 3′ portion of ALK starting with exon 20. Methods: Here, we report a novel EML4-ALK variant detected by reverse transcription polymerase chain reaction analysis. Results: Subsequent sequencing revealed an EML4-ALK fusion variant in which exon 6 of EML4 was fused to exon 19 of ALK. It occurred in a predominant solid pulmonary adenocarcinoma of a 65-year-old woman with a clear split signal of ALK in fluorescence in situ hybridization analysis and a weakly homogeneous ALK expression in immunohistochemical staining. Conclusions: Because of the growing number of fusion variants a primary reverse transcription polymerase chain reaction-based screening for ALK-positive non-small-cell lung carcinoma patients may not be sufficient for predictive diagnostics but transcript-based approaches and sequencing of ALK fusion variants might finally contribute to an optimized selection of patients.
Gesehen am 12.07.2018